A Filtration Based Technique for Simultaneous SEM and TEM Sample Preparation for the Rapid Detection of Pathogens - Beniac, Daniel R. (MDPI, 2014)
Diagnostic electron microscopy for infectious diseases has the advantage that “everything” in the specimen can be observed, without a priori knowledge of the likely identity of the microorganisms present in the sample. The classical specimen preparation method used employs a droplet of sample, which allows particles to adsorb to a support film, and is subsequently negative stained. This “grid on drop” procedure has a sensitivity range of approximately 10(6) viruses per mL if no enrichment procedures are used. In the current investigation we present a novel use of filtration that allows us to detect viruses at concentrations as low as 10(2) viruses per mL. We present here methods based on filtration, in which total virus, and not virus concentration, is the limiting factor for detection. We show that filtration is more sensitive than conventional negative staining and can detect as few as 5 × 10(3) particles per sample.